PELAKSANAAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DI LINGKUNGAN SEKOLAH - Ratna Julianti; Muhammad Nasirun; Wembrayarli Wembrayarli (Jurnal Ilmiah POTENSIA, 2018)
This study aims to describe how the implementation of clean and healthy life behavior (PHBS) in the school environment in the group B PAUD 'Aisyiyah 1 Arga Makmur. The research method used is descriptive quantitative. The population in this study were all children of PAUD 'Aisyiyah 1 Arga Makmur consisting of 16 children of group B. The instrument of this research is a questionnaire containing 43 questions. Analysis of statistical data by using the formula percentage. The results of the study on the implementation of clean and healthy life behavior (PHBS) in the school environment in the group B PAUD 'Aisyiyah 1 Arga Makmur that meet the criteria enough there are 3 people (18.75%) and 13 people (81.25%) the criteria is less. For that the researchers conclude that the implementation of clean and healthy life behavior (PHBS) in the school environment in the group B PAUD 'Aisyiyah 1 Arga Makmur children who studied have criteria with less average (K).